Association between residential exposure to road traffic noise and cognitive and motor function outcomes in children and preadolescents - Laura Pérez-Crespo; Mónica López-Vicente; Antònia Valentín; Miguel Burgaleta; Maria Foraster; Henning Tiemeier; Mònica Guxens (Environment International, 2024)
Background: Exposure to environmental noise is increasing in recent years but most of the previous literature in children has evaluated the effect of aircraft noise exposure at schools on cognition. Objective: To assess whether residential exposure to road traffic noise during pregnancy and childhood is associated with cognitive and motor function in children and preadolescents. Methods: The study involved 619 participants from the Spanish INMA-Sabadell cohort and 7,115 from the Dutch Generation R Study. We used noise maps to estimate the average day-evening-night road traffic noise levels at each participant’s residential address during pregnancy and childhood periods. Validated tests were administered throughout childhood in both cohorts to assess non-verbal and verbal intelligence, memory, processing speed, attentional function, working memory, cognitive flexibility, risky decision-making, and fine and gross motor function. Linear models, linear mixed models, and negative binomial models were run depending on the outcome in cohort-specific analysis and combined with a random-effects meta-analysis. All models were adjusted for several socioeconomic and lifestyle variables and results corrected for multiple testing. Results: Average road traffic noise exposure levels during pregnancy and childhood were 61.3 (SD 6.0) and 61.5 (SD 5.4) dB for the INMA-Sabadell cohort and 54.6 (SD 7.9) and 53.5 (SD 6.5) dB for the Generation R Study, respectively. Road traffic noise exposure during pregnancy and childhood was not related to any of the cognitive and motor function outcomes examined in this study (e.g. −0.92 (95 % CI −2.08; 0.24) and 0.20 (95 % CI −0.96; 1.35) in overall estimates of memory and fine motor function, respectively, when road traffic noise increases by 10 dB during childhood). Conclusions: These findings suggest that child’s cognitive or motor functions are not affected by residential exposure to road traffic noise. However, more studies evaluating this association at school and home settings as well as noise events are needed.